(3JaSjQ ZQjH eGaj cJGH SjHhjg ef GdCHfjIs - (3CHh MGJe Sgd Hf eMeO GdSLSJGfis; (3SjHhjg , YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3bGd GHh eMeO JaSjQ ZQjH eG ai cJGH SjHhjg ef GdGHfjI Yf CHj MGJe Sgd Hf eMeO GdSLSJGfi SeGYi efg bGd GHh MGJe GdNOd GdVNe Jbhd SGb NOdI s
(3BNQgG (B:s
(3JfJgi HCKfGA JaSjQ ZQjH HGH GdgeRI ef PcQ GdMGb GdRhGFO s
(3QhGjI GHf bJjHIs
(3YdjgG NWhW HYV GdYdeGAs
(3bhHdJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs